2013
DOI: 10.1111/dme.12238
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding in women with diabetes: lower rates despite greater rewards. A population‐based study

Abstract: Women with insulin-treated diabetes had the poorest outcomes with respect to breastfeeding rates. Gestational and non-insulin-treated diabetes were associated with lower rates of breastfeeding in hospital, while gestational diabetes was additionally associated with lower breastfeeding rates on discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(79 citation statements)
references
References 35 publications
1
73
0
1
Order By: Relevance
“…Important secondary findings in this study are the increase of factors that negatively affect breast feeding: in the SNQ register mothers of preterm infants in Sweden are reported to have more physical and mental illnesses in 2013 than in 2004, of which many (eg, mental illness,40 41 obesity,42 gestational diabetes)43 affect breast feeding negatively. The proportion of infants born SGA has increased from 2004 to 2013 and this increase was associated with a negative effect on exclusive breast feeding.…”
Section: Discussionmentioning
confidence: 81%
“…Important secondary findings in this study are the increase of factors that negatively affect breast feeding: in the SNQ register mothers of preterm infants in Sweden are reported to have more physical and mental illnesses in 2013 than in 2004, of which many (eg, mental illness,40 41 obesity,42 gestational diabetes)43 affect breast feeding negatively. The proportion of infants born SGA has increased from 2004 to 2013 and this increase was associated with a negative effect on exclusive breast feeding.…”
Section: Discussionmentioning
confidence: 81%
“…Despite recent trends of GDM, research investigating the relationship between GDM and breastfeeding is limited. To the authors' knowledge, two studies have been conducted on GDM and breastfeeding [13, 14], both of which utilized international samples. Results from a retrospective cohort analysis conducted in Ontario reported that women with GDM were less likely to breastfeed (odds ratio (OR) = 0.77; 95% confidence interval (CI) = 0.68–0.87) compared to women without GDM after controlling for potential confounders [13].…”
Section: Introductionmentioning
confidence: 99%
“…To the authors' knowledge, two studies have been conducted on GDM and breastfeeding [13, 14], both of which utilized international samples. Results from a retrospective cohort analysis conducted in Ontario reported that women with GDM were less likely to breastfeed (odds ratio (OR) = 0.77; 95% confidence interval (CI) = 0.68–0.87) compared to women without GDM after controlling for potential confounders [13]. Because of the differences in breastfeeding practices between countries and the demonstrated relationship between breastfeeding and infant outcomes for mothers with GDM [15, 16], further research is needed to understand the relationship between GDM and breastfeeding duration in the US.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The form of antenatal care provider has been found to influence the intention to breastfeed in women with diabetes (Finkelstein et al, 2013). For women in our study the frequent contacts with the antenatal care providers during pregnancy were abruptly interrupted when the child was born.…”
Section: Discussionmentioning
confidence: 99%